The lateral cerebral peduncle approach to ventrally placed intra-axial midbrain tumors: A technical note. (July 2021) - Shah, Abhidha; Jhawar, Sukhdeep Singh; Goel, Atul
Highlights: A novel safe entry point to approach ventral midbrain tumors is presented. The entry point is through the lateral one-fifth of the cerebral peduncle. The trajectory of the approach traverses the parieto-temporo-occipital pontine fibers. The trajectory is between the corticospinal tracts ventrally and the substantia nigra dorsally. Abstract: We describe the anatomical landmarks and surgical feasibility of a novel 'safe' brainstem entry zone to approach ventrally placed intra-axial midbrain tumors. The anatomy of the brainstem was specifically studied to evaluate safe surgical entry zone in the midbrain on two formalin fixed silicon injected cadaver head specimens. A novel entry point through the lateral one – fifth of the cerebral peduncle was identified to be 'safe' to approach lesions of the ventral midbrain. Three patients, having oculomotor schwannoma, peduncular glioma and a peduncular cavernoma were operated using this safe entry zone. To approach the midbrain, retrosigmoid lateral supracerebellar route was used in two patients and a basal subtemporal avenue was deployed in one patient. On the basis of fine microanatomical dissection on cadavers, a novel entry point through the lateral one-fifth of the cerebral peduncle, 5 mm anterior to the lateral mesencephalic sulcus and approximately 5 mm superior to the fourth nerve was identified. The proposed brainstem entry point traverses the parieto-temporo-occipital pontine fibers and the trajectory is between the corticospinal tracts ventrally and the substantia nigra dorsally. Three patients were operated successfully using the approach. There were no post-operative motor, sensory or extra-pyramidal deficits. The corridor through the lateral one-fifth of the cerebral peduncle presents a safe and relative 'easy' surgical route to approach ventrally placed intra-axial midbrain tumors.